Combined Effects of Elevated O3 Concentrations and Enhanced UV-B Radiation of the Biometric and Biochemical Properties of Soybean Roots - Mao, Bing; Wang, Yan; Zhao, Tian-Hong; Tian, Rong-Rong; Wang, Wei; Ye, Jia-Shu (Frontiers in Plant Science, 2017)
Enhanced ultraviolet-B (UV-B) radiation and elevated tropospheric ozone alone may inhibit the growth of agricultural crops. However, research regarding their combined effects on growth and biochemical properties of roots is still scarce. Using open top chambers, we monitored the response of growth, secondary metabolites, endogenous hormones and enzyme activities of soybean roots to elevated O3 and enhanced UV-B individually and in combination at stages of branching, flowering and podding. Our results indicated that the root biomass decreased by 23.6%, 25.2% and 27.7%, and root oxidative capacity declined by11.2%, 39.9% and 55.7% exposed to elevated O3, enhanced UV-B, and O3 + UV-B respectively, compared to the control treatment. Concentrations of quercetin and ABA were significantly increased, while concentrations of total polyphenol and P-coumaric acid responded insignificantly to elevated O3, enhanced UV-B, and O3 + UV-B during the whole period of soybean growth. Elevated O3, enhanced UV-B and O3+ UV-B showed significant negative effects on superoxide dismutase (SOD; EC 1.15.1.1) activity at flowering stage, on activities of peroxidase (POD; EC 1.11.1.7) and catalase (CAT; EC 1.11.1.6) at podding stage, on ascorbate peroxidase (APX) activity during the whole period of soybean growth. Moreover, compared to hormones and enzyme activity, secondary metabolisms showed stronger correlation with root growth exposed to elevated O3 and enhanced UV-B individually and in combination. Our study concluded that combined effects of O3 and UV-B radiation significantly exacerbated the decline of soybean root growth, and for annual legumes, the inhibited root growth exposed to O3 and/or UV-B radiation was mostly associated with secondary metabolisms (especially flavonoids).